Drivers of change in animal protein production systems: changes from 'traditional' to 'modern' beef cattle production systems in Brazil - Millen, Danilo Domingues [UNESP]; Arrigoni, Mário De Beni [UNESP] (Oxford University Press (OUP), 2013)
Until 1990, beef cattle production in Brazil was recognized as an enterprise of low investment, low cost of production, as well as an extensive production system that used large land areas to be economically feasible. The situation changed for the Brazilian beef market when the economy stabilized in 1994 and all sectors involved in the beef supply chain were able to predict their associated costs and profits. During the same period, purchasing power of the Brazilian population grew, and as a consequence, consumers began to demand higher quality beef products. This new scenario in the late 1990s and early 2000s has led to more intensive beef production systems in Brazil as well as the need for a greater understanding of how technologies might be applied. As consequence of this evolution, in the last five years, a necessity to increase beef production has occurred. The quality of Brazilian beef has improved compared with beef produced 15 years ago, but continued improvements are needed to achieve excellence in terms of large-scale production of high quality beef, be sustainable over a long period of time, and increase our contribution to global food security.